1984
DOI: 10.1002/jmor.1051820107
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional muscle model: A quantified relation between form and function of skeletal muscles

Abstract: A three-dimensional muscle model with complex geometry is described and tested against experimental data. Using this model, several muscles were constructed. These muscles have equal optimum length but differ in architecture. The force exerted by the constructed muscles, in relation to their actual length and velocity of shortening, is discussed. Generally speaking, the constructed muscles with considerable pennation have great fiber angles, a great physiological cross section, a narrow active and steep passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(109 citation statements)
references
References 25 publications
1
105
0
2
Order By: Relevance
“…To this point, isometric muscular length-force characteristics have been studied using isolated preparations of: (1) single isolated muscle fiber [3], (2) isolated fascicles [27], or (3) isolated whole muscle in situ [26]. Therefore, the possible role of the surrounding connective tissue in force transmission has largely been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…To this point, isometric muscular length-force characteristics have been studied using isolated preparations of: (1) single isolated muscle fiber [3], (2) isolated fascicles [27], or (3) isolated whole muscle in situ [26]. Therefore, the possible role of the surrounding connective tissue in force transmission has largely been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that any changes in this maximum stress value would directly influence the forces considered in the abdominal muscles for different cases. The passive tension-length relationship was also assumed to be the same for all the muscles despite the fact that the specific architecture of each muscle could influence this relationship [74]. The passive tension-length curve used in the current study was adapted from recent experimental data [25], which is in the range of those reported by others [48,58,74].…”
Section: Methodological Remarksmentioning
confidence: 99%
“…The passive tension-length relationship was also assumed to be the same for all the muscles despite the fact that the specific architecture of each muscle could influence this relationship [74]. The passive tension-length curve used in the current study was adapted from recent experimental data [25], which is in the range of those reported by others [48,58,74]. It is important to emphasize that the passive force-length and stiffness relations considered for muscles in the current study have absolutely no bearing at all on the predicted spinal loads and muscle forces.…”
Section: Methodological Remarksmentioning
confidence: 99%
“…Because of the particular arrangement of the sarcomeres within the muscle, the functional capabilities of the whole muscle can be different from those of the sarcomeres. In pennated muscles, fiber length change is less than muscle length change (Muhl, 1982;Woittiez et al, 1984), and the difference in length change increases with pennation angle. Several muscle models have been developed to account for the effects of different muscle architectures and to describe the relationship between muscle length changes and sarcomere length changes and the consequences for the production of relative force and excursion range (Otten, 1988;Kaufman et al, 1989;Spoor et al, 1991).…”
mentioning
confidence: 94%